Exosome Released FZD10 Increases Ki-67 Expression via Phospho-ERK1/2 in Colorectal and Gastric Cancer - Scavo, Maria Principia; Rizzi, Federica; Depalo, Nicoletta; Armentano, Raffaele; Coletta, Sergio; Serino, Grazia; Fanizza, Elisabetta; Pesole, Pasqua Letizia; Cervellera, Alessandra; Carella, Nicola; Curri, Maria Lucia; Giannelli, Gianluigi (Frontiers in Oncology, 2021)
Frizzled proteins (FZD) are primary receptors for Wnt signalling that activates the mitogen-activated protein kinase (MAPK) pathways. Disfunction of Wnt signals with consequently abnormal activation of MAPK3 pathways was found in CRC and GC. Up-regulation of FZD10 protein, localized in the exosomes isolated from plasma of CRC (Colorectal Cancer) and GC (Gastric Cancer) patients, was associated with a poor prognosis. Herein, the expression levels of circulating FZD10 were found to be strongly correlated to their expression levels in corresponding tissues, in CRC and GC patients. A bioinformatic prediction revealed a connection between FZD10 and Ki-67 through MAPK3. In both CRC and GC tissues, pERK1/2 levels were significantly increased at more advanced stage of disease and pERK1/2 and Ki-67 were correlated. Silencing of FZD10 in CRC and GC cells resulted in a significant reduction of pERK1/2 and Ki-67 expression, while subsequent treatment with exogenous exosomes partially restored their expression levels. The strong correlation between the expression of Ki-67 in tissues and of FZD10 in exosomes suggests that the exosome delivered FZD10 represents a promising novel prognostic and diagnostic biomarker for CRC and GC.